Students’ Learning Interest and Mathematical Literacy in Geometry: Evidence from Contextual Teaching and Learning at the Junior High School Level - Junianto Junianto; Muh Wildanul Firdaus; Katon Agung Ramadhan; Aulia Fonda; Junianto; Muh Wildanul Firdaus; Katon Agung Ramadhan (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
One of the problems in mathematics learning is the low level of students’ learning interest. Furthermore, the standard of education in Indonesia has not yet reached the level achieved by several other nations, as reflected in Indonesia’s scores and rankings in the PISA survey, which include mathematical literacy. The objective of this study is to assess the application of the Contextual Teaching and Learning (CTL) approach in the learning process to enhance students’ learning interest and mathematical literacy. This study employed a quasi-experimental design using a pretest–posttest control group framework. The participants comprised junior high school students from a public school in Yogyakarta, and two eight-grade groups as the sample, designated as the experimental and control groups. The instruments used were a learning interest questionnaire, a mathematical literacy test, and an observation sheet. Data were analyzed using Hotelling’s Trace and a one-sample t-test at a 5% significance threshold. The findings confirmed that CTL and expository approaches can enhance students’ learning interest and mathematical literacy. Furthermore, the comparative analysis revealed that the CTL approach demonstrated more optimal outcomes and had a significant impact compared to the expository approach in enhancing students’ learning interest and mathematical literacy.